PENGARUH JARAK TEMPUH DAN KONDISI TOPOGRAFI JALAN YANG DILEWATI KENDARAAN BERMOTOR RODA EMPAT TERHADAP KONSENTRASI EMISI HIDROKARBON (HC) DAN KARBON DIOKSIDA (CO2) (Studi Kasus : Mobil Dinas Camat di Kota Semarang) - Ramada Haqqo Mujtahida; Sri Sumiyati; Endro Sutrisno (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
The air in large cities exposed to a variety of pollutants. Of some kind of pollutant components, then the most influential in air pollution are the components of CO, NO, SO, HC and particles. Car is one of the sources of pollution in the air, the increasing number of cars that use the fuel, the emissions generated as hydrocarbons and carbon dioxide will increase. To ensure that the research done on the effect of distance and topography streets where automobiles to the concentration of HC and CO2 emissions.The method is carried out with the direct method of research in which direct conduct emissions testing on the sample car. Where the sample cars often pass through the area. And also conducted interviews directly to the owner of the car. From the analysis it can be seen the effect of the mileage and condition of the vehicle emission topography.The results showed that the farther the distance through which the vehicle is, the higher the HC and CO2emissions produced. But this has no effect on HC emissions vehicles often pass through areas with extreme topography. HC emissions generated on vehicles passing through the area with extreme topography higher than the vehicles passing through the area flat topography. As for the CO2, resulting in higher CO2 when passing through the higher elevations.